THE EFFECT OF ELECTRIC BREAST PUMP IN INCREASING BREASTMILK PRODUCTION - Sheyla Najwatul Maula Maula; Melyana Nurul Widyawati (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Breastfeeding for 2 years has been recommended by WHO and CDC, so that breastfeeding has become an integral part that determines the quality of human resources in the future as well as solutions for social, environmental and the economic problems faced by every nation around the world. This study was conducted as a preliminary study, the first step in the production of portable electric breast pumping equipment. One of the innovations in modifying electric breast pumping equipment that is more useful effective and efficient in various activities. Breast pumping equipment is a step in the transformational breastfeeding process because it can improve breastfeeding sustainability in the activity performed. Aims: To observe the effect of electric breast milk pump to the effectiveness and satisfaction in breast milk production in breastfeeding women in Semarang 2017. Methods: Preliminary study results were tested by statistical analysis test of independent sample T-Test and chi-square. Independent variable in this study is electric breast pump and dependent variables are effectiveness and satisfaction. This study was carried out by testing the electric breast milk Spectra 9+. The data were collected from 10 respondents. Results: The analysis test results showed the significance value P> 0.05 which meant that there was no significant difference between the effectiveness and satisfaction of breast milk production by using the electric breast pump. Conclusion: The electric breast pumping equipment have no effectiveness and satisfaction in milk production. Modification of electric breast milk pumping equipment should be expected to improve the use by postpartum women to breastfeed in various activities.